Symptoms, diagnosis and treatment of the acute porphyrias - Bianketti, Jolanta; Warzocha, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2006)
The acute porphyrias are a group of inherited disorders caused by deficiencies in activities of the enzymes of the heme biosynthetic pathway. The enzyme deficiencies lead to porphyrins, and their precursors, 5-aminolevulinic acid and porphobilinogen, are abnormally produced in excess, accumulate and the excreted. Abdominal pain, peripheral neuropathy and changes in mental status are the triad of an acute attack. Porphyrias are frequently misdiagnosed, because their symptoms may mimic other diseases. Haem therapy, started as soon as possible, is the most effective treatment. Early diagnosis, treatment and information about precipitating factors greatly improve prognosis, prevent development of neuropathic symptoms and diminish mortality.